2022
DOI: 10.1111/his.14819
|View full text |Cite
|
Sign up to set email alerts
|

Lung carcinoid tumours: histology and Ki‐67, the eternal rivalry

Abstract: Lung carcinoid tumours: histology and Ki-67, the eternal rivalry WHO classification of Thoracic Tumours defines lung carcinoid tumours (LCTs) as well-differentiated neuroendocrine neoplasms (NENs) classified in low grade typical (TC) and intermediate grade atypical carcinoids (AC). Limited data exist concerning protein expression and morphologic factors able to predict

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 23 publications
(54 reference statements)
0
16
0
Order By: Relevance
“…OTP was found to be an independent prognostic marker but better predicted patient outcome when combined with CD44, a stem cell marker and cellsurface glycoprotein. These findings were later validated by several other researchers resulting in the addition of coexpression of nuclear OTP and CD44 as a prognostic factor in the current WHO classification (1,10,(15)(16)(17).…”
Section: Value Of Orthopedia Homeobox Protein (Otp) Immunohistochemis...mentioning
confidence: 58%
See 1 more Smart Citation
“…OTP was found to be an independent prognostic marker but better predicted patient outcome when combined with CD44, a stem cell marker and cellsurface glycoprotein. These findings were later validated by several other researchers resulting in the addition of coexpression of nuclear OTP and CD44 as a prognostic factor in the current WHO classification (1,10,(15)(16)(17).…”
Section: Value Of Orthopedia Homeobox Protein (Otp) Immunohistochemis...mentioning
confidence: 58%
“…This suggests that OTP activation may be an important step for carcinoid tumorigenesis. However, downregulation seems to be related to tumor progression since loss of OTP protein expression correlates with prognosis ( 8 , 10 , 15 , 16 ). Recently, the authors of the paper commented on, examined DNA methylation data and found that that changes in DNA methylation patterns were associated with the difference in OTP expression levels ( 18 ).…”
Section: Value Of Orthopedia Homeobox Protein (Otp) Immunohistochemis...mentioning
confidence: 99%
“…Proliferative analysis also showed a specific role of Ki‐67 ≥10%, which was associated with reduced DFS. As previously proposed, Ki‐67 could represent an independent prognostic marker for carcinoids 23–26 . A recent study carried out by Marchiò et al .…”
Section: Discussionmentioning
confidence: 70%
“…As previously proposed, Ki-67 could represent an independent prognostic marker for carcinoids. [23][24][25][26] A recent study carried out by Marchi o et al showed a clinical role of Ki-67 10% cutoff for stratification of all lung carcinoid tumours and suggested that this cutoff is also reliable specifically for ACs identifying a subgroup with a dismal prognosis. 7 Our results underline that Ki-67 at 10% cutoff is a strong prognostic marker for ACs in univariate analysis, strongly associated with postoperative recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…24 However, there are some studies that did not find any significant association between hot spot Ki-67 and disease-free survival 25 or overall survival. 23 It is also interesting to note that Ki-67 is an independent predictor in multivariate models of some [26][27][28] but not all studies, 20,29 and thus the "added value" of Ki-67 in resected tumors remains ambiguous. The current WHO classification is certainly a strong predictor of outcome, 2,30,31 and its performance in predicting ds-PFS in the present study was statistically significant and comparable to Ki-67.…”
Section: Discussionmentioning
confidence: 99%